Concerted Catalysis by Adjacent Palladium and Gold in Alloy Nanoparticles for the Versatile and Practical [2+2+2] Cycloaddition of Alkynes. (27th April 2018) - Miura, Hiroki; Tanaka, Yumi; Nakahara, Karin; Hachiya, Yuka; Endo, Keisuke; Shishido, Tetsuya
Abstract: A Pd‐Au alloy efficiently catalyzed the [2+2+2] cycloaddition of substituted alkynes. Whereas monometallic Pd and Au catalysts were totally ineffective, Pd‐Au alloy nanoparticle catalysts with a low Pd/Au molar ratio showed high activity to give the corresponding polysubstituted arenes in high yields. A variety of substituted alkynes participated in various modes of cycloaddition under Pd‐Au alloy catalysis. The Pd‐Au alloy catalysts exhibited high air tolerance and reusability. Abstract : Konzertierte Katalyse durch Pd und Au in legierten Nanopartikeln ermöglicht die effiziente [2+2+2]‐Cycloaddition von substituierten Alkinen zu polysubstituierten Arenen. Eine Vielzahl von Alkinen kann in verschiedenen Arten von Cycloadditionen unter Pd‐Au‐Katalyse umgesetzt werden. Die Pd‐Au‐Katalysatoren sind luftstabil und wiederverwendbar.